Copolymer

By developing a conductive copolymer that can improve the performance of the secondary battery in a normal state but prevent short circuit and overheating in an abnormal state, the risk of explosion and fire in the secondary battery during overcharging, high temperature exposure or external impact is solved, and the stability and safety of the battery are achieved.

CN119768450APending Publication Date: 2025-04-04LG CHEM LTD +1
View PDF 1 Cites 0 Cited by

Patent Information

Application Number
CN202380061024.5
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Priority Date
2022-10-19
Filing Date
2023-10-19
Publication Date
2025-04-04

AI Technical Summary

Technical Problem

Existing secondary batteries are prone to short-circuiting when overcharging, high temperature exposure or external impact, resulting in an increased risk of ignition or explosion.

Method used

A conductive copolymer is developed that exhibits low resistance in normal state to improve the performance of secondary batteries, but can form current collectors, electrodes and secondary batteries in abnormal states to ensure stability. This copolymer suppresses abnormal charge flow and prevents short circuits and overheating by controlling the PTC effect and oxidation potential.

Benefits of technology

It effectively reduces the risk of explosion and fire of secondary batteries in abnormal states, ensures the stability and safety of the battery, and does not affect the performance of the battery under normal states.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119768450A_ABST
    Figure CN119768450A_ABST
Patent Text Reader

Abstract

The present specification discloses a copolymer and a use thereof. The copolymer may exhibit a PTC (Positive Temperature Coefficient) effect and oxidation potential that are controlled according to the purpose. This conductive copolymer can improve the performance and operation of a secondary battery by exhibiting excellent electrical properties such as low resistance without affecting or instead in a normal state, and can form a current collector for an electrode, an electrode, and a secondary battery including the same in an abnormal state, which can secure stability. The present specification also discloses a use of the copolymer.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] CROSS-REFERENCE TO RELATED APPLICATIONS

[0002] This application claims the benefit of priority based on Korean Patent Application No. 10-2022-0134842 filed on October 19, 2022, the disclosure of which is incorporated herein by reference in its entirety. Technical Field

[0004] The present invention discloses a copolymer and its use. Background Art

[0005] Energy storage technology has expanded its application areas to mobile phones, tablets and laptops, or electric vehicles.

[0006] As the data processing speed of mobile devices such as mobile phones or tablets increases and their usage hours also increase, secondary batteries having high energy density and operating potential, long cycle life, and low self-discharge rate are being developed.

[0007] Furthermore, as major developed countries curb production of automobiles driven by internal combustion engines to mitigate global warming and air pollution, major automobile manufacturers are also developing various electric vehicles, and thus the importance of secondary batteries having high energy density, high discharge voltage, and output stability as their driving sources is increasing.

[0008] However, according to the above-mentioned trend, in devices or automobiles using secondary batteries as energy sources, the frequency of occurrence of fire or explosion accidents due to overcharging, high temperature exposure, external impact, or the like is also increasing.

[0009] As a major cause of such accidents, a short circuit phenomenon is known in which the positive electrode and the negative electrode inside the electrode assembly directly contact each other mainly due to external stimulation. When the secondary battery is overcharged or exposed to high temperature or external stimulation, the short circuit phenomenon may occur due to the shrinkage of the diaphragm caused by the increase in the internal temperature of the secondary battery, or the destruction of the internal structure of the secondary battery due to external impact, etc.

[0010] When a short circuit occurs, the migration of lithium ions and electrons is concentrated through the area where the positive electrode and the negative electrode are in direct contact with each other, which can promote internal heat generation. Therefore, it is known that as gas is generated inside the battery, the volume expands and the risk of fire increases. Summary of the invention

[0011] Technical issues

[0012] This specification discloses a copolymer and its use. This specification is intended to disclose a conductive copolymer that exhibits a PTC (positive temperature coefficient) effect and an oxidation potential controlled according to a purpose. This conductive copolymer does not affect or can improve the performance and operation of a secondary battery by exhibiting excellent electrical properties such as low resistance under normal conditions, and can form a current collector, an electrode and a secondary battery for an electrode including it under abnormal conditions, which can ensure stability. This specification also intends to disclose a use of the copolymer.

[0013] Technical Solution

[0014] In this specification, the term room temperature refers to a natural temperature without heating or cooling, wherein the room temperature may be, for example, any temperature within the range of 10°C to 30°C, or a temperature of about 23°C, about 25°C or about 27°C.

[0015] Among the physical properties mentioned in this specification, when measuring the influence of temperature on the physical properties, the relevant physical properties are the physical properties measured at room temperature unless otherwise specified.

[0016] The temperature unit in this specification is Celsius (°C) unless otherwise specified.

[0017] In the present specification, the term normal pressure refers to a natural pressure without pressurization or reduction, which may generally refer to a pressure of about 730 mmHg to 790 mmHg.

[0018] Among the physical properties mentioned in this specification, when measuring the pressure affecting the physical properties, the relevant physical properties are the physical properties measured under normal pressure, unless otherwise specified.

[0019] Among the physical properties mentioned in this specification, when measuring humidity affects the results, the relevant physical properties are the physical properties measured at humidity under standard conditions, unless otherwise specified.

[0020] Humidity under standard conditions refers to any relative humidity in the range of 40% to 60%, which means, for example, a relative humidity of around 55%, or 60%.

[0021] In this specification, the term normal state refers to a normal operating state of a secondary battery (eg, a normal charging or discharging state of the secondary battery) or a storage state thereof.

[0022] In this specification, the term abnormal state refers to a dangerous state in which abnormal charge flow, abnormal heat generation, explosion, etc. occurs due to external impact and / or a short circuit phenomenon, etc., or a dangerous state in which the probability of occurrence of such an abnormal state increases.

[0023] This specification discloses a copolymer.

[0024] The copolymer may exhibit a PTC (positive temperature coefficient) effect and an oxidation potential which are precisely controlled according to the purpose.

[0025] The PTC (positive temperature coefficient) effect is an effect in which resistance increases according to temperature. Therefore, if the PTC effect of the conductive copolymer is designed to be inactive or suppressed at a temperature under normal conditions and then appear under abnormal conditions, the stability of the secondary battery can be ensured by suppressing abnormal charge flow.

[0026] Furthermore, by adjusting the oxidation potential of the conductive copolymer, a secondary battery to which the copolymer is applied can be stably operated when charging and discharging and high-speed charging and discharging are repeated in a normal state.

[0027] The copolymer includes at least two different monomer units. In the present specification, unless specifically defined otherwise, the term monomer unit refers to a structure in which a monomer is polymerized and included in the copolymer.

[0028] The copolymer may be a polythiophene or a thiophene polymer. In this specification, the term polythiophene or thiophene polymer refers to a polymer containing a thiophene unit above a certain level. In this specification, the term thiophene unit refers to a monomer unit formed by polymerizing a thiophene-based monomer, and a thiophene-based monomer refers to a monomer containing a thiophene skeleton.

[0029] Based on the total moles of all monomer units in the polythiophene or thiophene polymer, the lower limit of the proportion of thiophene units in the polythiophene or thiophene polymer may be about 10 mol%, 15 mol%, 20 mol%, 25 mol%, 30 mol%, 35 mol%, 40 mol%, 45 mol%, 50 mol%, 55 mol%, 60 mol%, 65 mol%, 70 mol% or 75 mol%, and the upper limit thereof may be about 99 mol%, 97 mol%, 95 mol%, 93 mol%, 91 mol%, 89 mol%, 87 mol%, 85 mol%, 83 mol%, 81 mol%, 79 mol%, 77 mol%, 75 mol%, 73 mol%, 71 mol%, 69 mol%, 67 mol%, 65 mol%, 63 mol%, 61 mol%, 59 mol%, 57 mol%, 55 mol%, 53 mol% or 51 mol%. The proportion of thiophene units in the polythiophene or thiophene polymer may be within a range greater than or equal to or greater than any one of the above lower limits; or may be within a range less than or equal to or less than any one of the above upper limits and greater than or equal to or greater than any one of the above lower limits.

[0030] As the thiophene unit, a thiophene unit having a hydrocarbon functional group can be applied. In this specification, the term hydrocarbon functional group refers to a monovalent hydrocarbon group (i.e., a monovalent functional group consisting of carbon and hydrogen), or a monovalent functional group containing a monovalent hydrocarbon group. Therefore, in addition to carbon and hydrogen, the hydrocarbon functional group may also contain other atoms.

[0031] The lower limit of the carbon number of the hydrocarbon functional group or the monovalent hydrocarbon group may be about 3, 4, 5, 6, 7, 8, 9, 10, 11 or 12, and the upper limit thereof may be about 20, 19, 18, 17, 16, 15, 14, 13, 12, 11, 10, 9, 8, 7, 6, 5, 4 or 3. The carbon number of the hydrocarbon functional group or the monovalent hydrocarbon group may be in a range greater than or equal to or greater than any one of the above lower limits; or in a range less than or equal to or less than any one of the above upper limits; or may have a range between less than or equal to or less than any one of the above upper limits and greater than or equal to or greater than any one of the above lower limits.

[0032] The carbon number may be the total carbon number present in the hydrocarbon functional group or the monovalent hydrocarbon group, or the carbon number of the hydrocarbon chain having a straight chain structure included in the hydrocarbon functional group or the monovalent hydrocarbon group. That is, the hydrocarbon functional group or the monovalent hydrocarbon group may have a straight chain structure or a branched chain structure, and even in the case of a branched chain structure, the carbon number constituting the longest straight chain in the branched chain structure may be within the above range. For example, if the branched chain structure is 2-ethylhexyl, the carbon number constituting the longest chain is 6 included in the hexyl chain.

[0033] Examples of monovalent hydrocarbon groups may include alkyl, alkynyl or alkenyl, and examples of hydrocarbon functional groups may include alkyl, alkenyl, alkynyl, alkoxy, alkylcarbonyl, or alkylcarbonyloxy, etc., but are not limited thereto. In suitable examples, the hydrocarbon functional group may be alkyl and / or alkoxy.

[0034] The number of carbons present in the alkyl group, alkenyl group, alkynyl group, alkoxy group, alkyl group of alkylcarbonyl group, and alkyl group of alkylcarbonyloxy group may be within the range of the number of carbons present in the hydrocarbon functional group or the monovalent hydrocarbon group.

[0035] For example, an alkyl group, an alkenyl group, an alkynyl group, an alkoxy group, an alkyl group of an alkylcarbonyl group, and an alkyl group of an alkylcarbonyloxy group may have a straight chain or a branched chain structure, and in the case of a branched chain, the number of carbon atoms constituting the longest straight chain in the relevant branched chain structure may be within the range of the number of carbon atoms existing in the hydrocarbon functional group or the monovalent hydrocarbon group.

[0036] The alkyl, alkenyl, alkynyl, alkoxy, alkylcarbonyl or alkylcarbonyloxy groups as hydrocarbon functional groups may also be optionally substituted by one or more substituents.

[0037] In the conductive copolymer, the lower limit of the molar ratio of the thiophene unit having a hydrocarbon functional group may be about 30 mol%, 35 mol%, 40 mol%, 45 mol%, 50 mol%, 55 mol%, 60 mol%, 65 mol% or 70 mol%, and the upper limit thereof may be about 95 mol%, 90 mol%, 85 mol%, 80 mol%, 75 mol%, 70 mol%, 65 mol%, 60 mol%, 55 mol%, 50 mol% or 45 mol%. The ratio is based on the total molar number of all monomer units contained in the copolymer. The ratio may be in a range greater than or equal to or greater than any one of the above lower limits; or in a range less than or equal to or less than any one of the above upper limits; or may also have a range between less than or equal to or less than any one of the above upper limits and greater than or equal to or greater than any one of the above lower limits.

[0038] At such a ratio, the conductive copolymer or polymer layer exhibits an appropriate PTC (positive temperature coefficient) effect and its surface characteristics are adjusted, thereby ensuring excellent adhesion in an electrode or a current collector for an electrode and exhibiting an appropriate level of oxidation potential.

[0039] The hydrocarbon functional group is a functional group that can impart appropriate fluidity to the polymerization process of the conductive polymer or the conductive polymer itself. This functional group imparts appropriate fluidity to the monomer mixture and diffuses in the monomer mixture so that polymerization can occur with excellent efficiency. In addition, the conductive polymer having the functional group can stably and uniformly form a polymer layer between the current collector body and the active material layer through appropriate fluidity.

[0040] The hydrocarbon functional groups are properly oriented in a drying or annealing process (heat treatment process) applied during the formation of the polymer layer, whereby it is also possible to impart suitable PTC effect and oxidation potential characteristics to the copolymer.

[0041] When a certain amount of thermal energy is applied, the hydrocarbon functional group vibrates due to heat, and the dedoping of the anions bound to the copolymer is promoted by the vibration (thermal vibration), thereby causing an increase in resistance. The temperature at which the thermal vibration occurs can be controlled by the length and / or amount of the hydrocarbon functional group. For example, at the same temperature, the thermal vibration of a relatively long chain is greater than the thermal vibration of a relatively short chain, so that the long chain can cause a resistance increase effect at a relatively low temperature. Therefore, the desired PTC effect can be set by controlling the length and / or ratio of the hydrocarbon functional group.

[0042] As the thiophene unit, the copolymer may include a first thiophene unit having a long-chain hydrocarbon functional group and a second thiophene unit having a short-chain hydrocarbon functional group.

[0043] In the present specification, the term long-chain hydrocarbon functional group refers to a hydrocarbon functional group having the above-mentioned carbon number at a certain level or more and belonging to the category of hydrocarbon functional groups as described above.

[0044] In the present specification, the term short-chain hydrocarbon functional group refers to a hydrocarbon functional group having the above-mentioned carbon number below a certain level and belonging to the category of hydrocarbon functional groups as described above.

[0045] The lower limit of the carbon number of the long-chain hydrocarbon group may be about 10, 11 or 12, and the upper limit thereof may also be about 20, 19, 18, 17, 16, 15, 14, 13, 12, 11 or 10. The carbon number contained in the long-chain hydrocarbon group may be in a range greater than or equal to or greater than any one of the above lower limits; or may have a range between less than or equal to or less than any one of the above upper limits and greater than or equal to or greater than any one of the above lower limits.

[0046] The lower limit of the carbon number of the short-chain hydrocarbon group may be about 3, 4, 5, 6, 7 or 8, and the upper limit thereof may also be about 9, 8, 7 or 6. The carbon number contained in the short-chain hydrocarbon group may be in a range less than or equal to or less than any one of the above upper limits; or may be in a range between less than or equal to or less than any one of the above upper limits and greater than or equal to or greater than any one of the above lower limits.

[0047] Regarding the long-chain and short-chain hydrocarbon functional groups, matters other than the above-mentioned carbon number, for example, the meaning of the carbon number, the specific type of the functional group, etc. follow the contents described for the hydrocarbon functional groups.

[0048] Thus, for example, the carbon number may be the total carbon number present in the long-chain and short-chain hydrocarbon functional groups, or the carbon number of the hydrocarbon chain having a straight-chain structure included in the functional group. For example, the monovalent hydrocarbon group present in the long-chain and short-chain hydrocarbon functional groups may have a straight-chain structure or a branched structure, and even in the case of a branched structure, the carbon number constituting the longest straight chain in the relevant branched structure may be within the above range. For example, if the branched structure is 2-ethylhexyl, the carbon number constituting the longest chain is 6.

[0049] In addition, examples of long-chain and short-chain hydrocarbon functional groups can be exemplified by one or more selected from alkyl, alkenyl, alkynyl, alkoxy, alkylcarbonyl and alkylcarbonyloxy. In suitable examples, the long-chain and short-chain hydrocarbon functional groups can be alkyl and / or alkoxy.

[0050] The number of carbons present in the alkyl group, alkenyl group, alkynyl group, alkoxy group, alkyl group of alkylcarbonyl group, and alkyl group of alkylcarbonyloxy group can be within the range of the number of carbons present in the long chain or short chain hydrocarbon functional group.

[0051] The alkyl, alkenyl, alkynyl, alkoxy, alkylcarbonyl or alkylcarbonyloxy groups as hydrocarbon functional groups may also be optionally substituted by one or more substituents.

[0052] In the conductive copolymer, the lower limit of the ratio of the total molar number of the first thiophene unit and the second thiophene unit may be about 30 mol%, 35 mol%, 40 mol%, 45 mol%, 50 mol%, 55 mol%, 60 mol%, 65 mol% or 70 mol%, and the upper limit thereof may be about 95 mol%, 90 mol%, 85 mol%, 80 mol%, 75 mol%, 70 mol%, 65 mol%, 60 mol%, 55 mol%, 50 mol% or 45 mol%. The ratio is based on the total molar number of all monomer units contained in the copolymer. The ratio may be in a range less than or equal to or less than any one of the above upper limits; or in a range greater than or equal to or greater than any one of the above lower limits; or may also have a range between less than or equal to or less than any one of the above upper limits and greater than or equal to or greater than any one of the above lower limits.

[0053] The lower limit of the ratio (M2 / M1) of the number of moles of thiophene units (M2) having a short-chain hydrocarbon functional group to the number of moles of thiophene units (M1) having a long-chain hydrocarbon functional group in the conductive copolymer may be about 0.01, 0.05, 0.1 or 0.5, and the upper limit thereof may be about 100, 95, 90, 85, 80, 75, 70, 65, 60, 55, 50, 45, 40, 35, 30, 25, 20, 15, 10, 9, 8, 7, 6, 5, 4, 3, 2, 1, 0.8, 0.7, 0.6 or 0.55. The ratio may be in a range of less than or equal to or less than any one of the above upper limits; or in a range of greater than or equal to or greater than any one of the above lower limits; or may also have a range between less than or equal to or less than any one of the above upper limits and greater than or equal to or greater than any one of the above lower limits.

[0054] At such a ratio, the conductive copolymer or polymer layer exhibits an appropriate PTC (positive temperature coefficient) effect, and its surface characteristics are adjusted, thereby making it possible to ensure excellent adhesion in an electrode or a current collector for an electrode.

[0055] The copolymer may further include a thiophene unit having a polar functional group together with the thiophene unit having a hydrocarbon functional group as the thiophene unit.

[0056] In this specification, the term polar functional group is a functional group containing one or two or more polar atoms, for example, oxygen and / or nitrogen. Examples of such functional groups include carboxyl, hydroxyl, amino, cyano, nitro, ether or the functional group of Formula 4 below, but are not limited thereto.

[0057] [Formula 4]

[0058]

[0059] In Formula 4, L3 is a single bond, an alkylene group or an alkylidene group, L4 is an alkylene group or an alkylidene group, R8 is hydrogen or an alkyl group, and n is an arbitrary number.

[0060] In Formula 4, the matter that L3 is a single bond refers to a form in which L3 does not exist, and the oxygen atom between L4 and L3 is connected to the skeleton of the monomer or polymer.

[0061] In the present specification, the term alkylene group refers to a divalent functional group formed by respectively removing hydrogen atoms from two different carbon atoms in an alkane, and the term alkylidene group refers to a divalent functional group formed by removing two hydrogen atoms from one carbon atom in an alkane.

[0062] In the present specification, unless otherwise specifically defined, the term alkylene may be an alkylene having 2 to 20 carbon atoms, 2 to 16 carbon atoms, 2 to 12 carbon atoms, 2 to 8 carbon atoms, or 2 to 4 carbon atoms. The alkylene may be linear or branched or cyclic, and it may also be optionally substituted by one or more substituents.

[0063] In this specification, unless otherwise specifically limited, the term alkylidene group may be an alkylidene group having 1 to 20 carbon atoms, 1 to 16 carbon atoms, 1 to 12 carbon atoms, 1 to 8 carbon atoms, or 1 to 4 carbon atoms. The alkylidene group may be linear or branched or cyclic, and it may also be optionally substituted by one or more substituents.

[0064] In one example, the alkyl group of R8 in Formula 4 may be an alkyl group having 1 to 20 carbon atoms, 1 to 16 carbon atoms, 1 to 12 carbon atoms, 1 to 8 carbon atoms, or 1 to 4 carbon atoms, or may be a methyl group or an ethyl group. The alkyl group may be linear, branched, or cyclic, and may be linear or branched as appropriate.

[0065] The lower limit of n in Formula 4 may be about 1, 2, 3 or 4, and the upper limit thereof may be about 10, 9, 8, 7, 6, 5, 4 or 3. n may be in a range less than or equal to or less than any one of the above upper limits; or in a range greater than or equal to or greater than any one of the above lower limits; or may have a range between less than or equal to or less than any one of the above upper limits and greater than or equal to or greater than any one of the above lower limits.

[0066] By applying the polar functional group, the polymer layer including the conductive polymer can be bonded to other layers to have an appropriate bonding force, and the desired protective function can be effectively achieved by uniformly forming the conductive polymer layer.

[0067] In the case where the thiophene unit having a polar functional group exists in the conductive copolymer, the thiophene unit having a polar functional group may exist such that the total number of moles of the thiophene unit having a hydrocarbon functional group per mole of the thiophene unit having a polar functional group is within a predetermined range.

[0068] For example, the lower limit of the total molar number of thiophene units having a hydrocarbon functional group per mole of thiophene units having a polar functional group may be about 1 mol, 2 mol, 3 mol, 4 mol, 5 mol, 6 mol, 7 mol, 8 mol, 8.5 mol or 9 mol, and the upper limit thereof may be about 500 mol, 450 mol, 400 mol, 350 mol, 300 mol, 250 mol, 200 mol, 150 mol, 100 mol, 95 mol, 90 mol, 85 mol, 80 mol, 75 mol, 70 mol, 65 mol, 60 mol, 55 mol, 50 mol, 45 mol, 40 mol, 35 mol, 30 mol, 25 mol, 20 mol, 15 mol, 10 mol, 9.5 mol or 9 mol. The ratio may be within a range of less than or equal to or less than any one of the above upper limits; or within a range of greater than or equal to or greater than any one of the above lower limits; or may have a range between less than or equal to or less than any one of the above upper limits and greater than or equal to or greater than any one of the above lower limits.

[0069] Such a thiophene unit may be, for example, a unit of Formula 1 below.

[0070] [Formula 1]

[0071]

[0072] In Formula 1, R1 and R2 may each independently be hydrogen, a polar functional group or a hydrocarbon functional group.

[0073] In another example, R1 and R2 of Formula 1 may also be connected to each other to form a divalent functional group of Formula 2 below.

[0074] [Formula 2]

[0075]

[0076] In Formula 2, L1 and L2 may each independently be a single bond, an alkylene group or an alkylidene group, and R3 and R4 may each independently be hydrogen, a polar functional group or a hydrocarbon functional group.

[0077] For example, if the unit of Formula 1 is a thiophene unit having a hydrocarbon functional group as described above, one or more of R1 and R2 may be a hydrocarbon functional group (if R1 and R2 are not connected), or one or more of R3 and R4 may be a hydrocarbon functional group (if R1 and R2 are not connected).

[0078] For example, if the unit of Formula 1 is a thiophene unit having a polar functional group as described above, one or more of R1 and R2 may be a polar functional group (if R1 and R2 are not connected), or one or more of R3 and R4 may be a polar functional group (if R1 and R2 are not connected).

[0079] For example, if the unit of Formula 1 above is a thiophene unit having a long-chain hydrocarbon functional group as described above, one or more of R1 and R2 may be the above-mentioned long-chain hydrocarbon functional group (if R1 and R2 are not connected), or one or more of R3 and R4 may be the above-mentioned long-chain hydrocarbon functional group (if R1 and R2 are not connected).

[0080] For example, if the unit of Formula 1 above is a thiophene unit having a short-chain hydrocarbon functional group as described above, one or more of R1 and R2 may be the above-mentioned short-chain hydrocarbon functional group (if R1 and R2 are not connected), or one or more of R3 and R4 may be the above-mentioned short-chain hydrocarbon functional group (if R1 and R2 are not connected).

[0081] Specific descriptions of the hydrocarbon functional group, polar functional group, long-chain hydrocarbon functional group and short-chain hydrocarbon functional group are as described above.

[0082] The specific description of the alkylene group and the alkylidene group of the above Chemical Formula 2 is as described in the above Formula 4.

[0083] The copolymer may comprise another additional monomer unit together with the thiophene unit. For example, the additional monomer may be included to adjust the oxidation potential of the copolymer.

[0084] As such a monomer, for example, pyrrole or a monomer containing its skeleton can be exemplified. Such a monomer can play a role in reducing high oxidation potential due to the thiophene unit.

[0085] For example, the copolymer may include a unit of the following Formula 3 and a thiophene unit.

[0086] [Formula 3]

[0087]

[0088] In Formula 3, R5, R6 and R7 are each independently hydrogen, a polar functional group or a hydrocarbon functional group. Here, the specific details of the polar functional group and the hydrocarbon functional group are as described for the thiophene unit.

[0089] The copolymer in which the above units are simultaneously present can exhibit an appropriate oxidation potential together with the PTC effect. Therefore, the copolymer can be applied to an electrode to induce stable operation of a secondary battery without increasing resistance in a normal state.

[0090] The proportion of the units of formula 3 in the copolymer is adjusted according to the desired PTC effect and / or oxidation potential, and is not particularly limited.

[0091] In one example, the lower limit of the ratio of the unit of formula 3 in the copolymer can be about 1 mol%, 5 mol%, 10 mol%, 15 mol%, 20 mol%, 25 mol%, 30 mol%, 35 mol%, 40 mol%, 45 mol% or 50 mol%, and the upper limit can be about 95 mol%, 90 mol%, 85 mol%, 80 mol%, 75 mol%, 70 mol%, 65 mol%, 60 mol%, 55 mol%, 50 mol%, 45 mol%, 40 mol%, 35 mol%, 30 mol%, 25 mol% or 20 mol%. The ratio is based on the total molar number of all monomer units contained in the copolymer. The ratio can be less than or equal to or less than any one of the above upper limits; or in a range greater than or equal to or greater than any one of the above lower limits; or it can also have a range between less than or equal to or less than any one of the above upper limits and greater than or equal to or greater than any one of the above lower limits.

[0092] In the copolymer, the lower limit of the ratio of the total molar number of the thiophene unit and the above-mentioned formula 3 unit can be about 50 mol%, 55 mol%, 60 mol%, 65 mol%, 70 mol%, 75 mol%, 80 mol%, 85 mol% or 90 mol%, and the upper limit can be about 100 mol% or 95 mol%. The ratio is based on the total molar number of all monomer units contained in the copolymer. The ratio can be within a range of less than or equal to or less than any one of the above upper limits; or within a range of greater than or equal to or greater than any one of the above lower limits; or it can also have a range between less than or equal to or less than any one of the above upper limits and greater than or equal to or greater than any one of the above lower limits.

[0093] The copolymer may further contain other monomer units within a range not impairing the desired effects (eg, PTC effect and / or oxidation potential).

[0094] The copolymer may have a weight average molecular weight (Mw) within a predetermined range. The lower limit of the weight average molecular weight of the copolymer may be about 10,000 g / mol, 20,000 g / mol, 30,000 g / mol, 40,000 g / mol, 50,000 g / mol, 60,000 g / mol, 70,000 g / mol, 80,000 g / mol, 90,000 g / mol or 100,000 g / mol, and the upper limit may be 2,000,000 g / mol, 1,500,000 g / mol, 1,000,000 g / mol, 900,000 g / mol. l, 800,000g / mol, 700,000g / mol, 600,000g / mol, 500,000g / mol, 400,000g / mol, 300,000g / mol, 295,000g / mol, 290,000 g / mol, 285,000g / mol, 280,000g / mol, 275,000g / mol, 270,000g / mol, 265,000g / mol, 260,000g / mol, 255,000g / mol, 250, 000g / mol, 245,000g / mol, 240,000g / mol, 235,000g / mol, 230,000g / mol, 225,000g / mol, 220,000g / mol, 215,000g / mol, 210,000g / mol, 205,000g / mol, 200,000g / mol, 195,000g / mol, 190,000g / mol, 185,000g / mol, 180,000g / mol, 175,000g / The weight average molecular weight may be about 100,000 g / mol, 150,000 g / mol, 160,000 g / mol, 170,000 g / mol, 165,000 g / mol, 160,000 g / mol, 155,000 g / mol, 150,000 g / mol, 145,000 g / mol, 140,000 g / mol, 135,000 g / mol, 130,000 g / mol, 125,000 g / mol, 120,000 g / mol, 115,000 g / mol, 110,000 g / mol, 105,000 g / mol or 100,000 g / mol. The weight average molecular weight may be in a range less than or equal to or less than any one of the above upper limits; or in a range greater than or equal to or greater than any one of the above lower limits; or may also have a range between less than or equal to or less than any one of the above upper limits and greater than or equal to or greater than any one of the above lower limits.

[0095] The molecular weight distribution of the copolymer, i.e., the ratio of the weight average molecular weight (Mw) to the number average molecular weight (Mn), may be within a predetermined range. The lower limit of the molecular weight distribution may be about 2, 2.5, 3, 3.5, or 4, and the upper limit thereof may be about 8, 7.5, 7, 6.5, 6, 5.5, 5, 4.5, or 4. The molecular weight distribution may be within a range of less than or equal to or less than any one of the above upper limits; or within a range of greater than or equal to or greater than any one of the above lower limits; or may also have a range between less than or equal to or less than any one of the above upper limits and greater than or equal to or greater than any one of the above lower limits.

[0096] The weight average molecular weight and molecular weight distribution are measured in the manner described in "2. GPC (Gel Permeation Chromatography)" in the Example section of this specification.

[0097] The copolymers can exhibit controlled oxidation potentials. For example, the lower limit of the oxidation potential of the copolymer can be about 0V, 0.1V, 0.2V, 0.3V, 0.4V, 0.5V, 0.6V, 0.7V, 0.8V, 0.9V, 1.0V, 1.1V, 1.2V, 1.3V, 1.4V, 1.5V, 1.6V, 1.7V, 1.8V, 1.9V, 2.0V, 2.1V, 2.2V, 2.3V, 2.4V, 2.5V, 2.6V, 2.7V, 2.8V, 2.9V, 3V, 3.1V, 3.2V, 3.3V, 3.4V, 3.5V, 3.6V, 3.7V, 3.8V or 3.9V, and the upper limit can be about 6.0V, 5.5V, 5V, 4.5V, 4.0V or 3.9V. The oxidation potential may be within a range of less than or equal to or less than any one of the above upper limits; or may also be within a range of less than or equal to or less than any one of the above upper limits and greater than or equal to or greater than any one of the above lower limits. The oxidation potential of the copolymer is the oxidation potential relative to lithium, which is based on the oxidation potential of lithium and lithium ions (Li / Li + ) The method for measuring the oxidation potential is described in "4. Oxidation potential measurement method of copolymer" in the Example section of this specification.

[0098] In one example, the upper limit of the DC resistance of the copolymer at 25°C may be 10 4Ω·cm, 9500Ω·cm, 9000Ω·cm, 8500Ω·cm, 8000Ω·cm, 7500Ω·cm, 7000Ω·cm, 6500Ω·cm, 6000Ω·cm, 5500Ω·cm , 5000Ω·cm, 4500Ω·cm, 4000Ω·cm, 3500Ω·cm, 3000Ω·cm, 2500Ω·cm, 2000Ω·cm, 1500Ω·cm, 1000Ω·cm, 950Ω ·cm, 900Ω·cm, 850Ω·cm, 800Ω·cm, 750Ω·cm, 700Ω·cm, 650Ω·cm, 600Ω·cm, 550Ω·cm, 500Ω·cm, 450Ω·cm or about 400Ω·cm, and the lower limit may be about 10Ω·cm, 50Ω·cm, 100Ω·cm, 150Ω·cm, 200Ω·cm, 250Ω·cm, 300Ω·cm, 350Ω·cm or about 400Ω·cm. The DC resistance may be in a range less than or equal to or less than any one of the above upper limits; or it may also have a range between less than or equal to or less than any one of the above upper limits and greater than or equal to or greater than any one of the above lower limits. The DC resistance is measured in the manner described in "6. DC resistance measurement method" of the embodiments of this specification.

[0099] The upper limit of the AC impedance resistance of the copolymer can be 10 3 The AC impedance resistance may be within a range of less than or equal to or less than any one of the above upper limits; or may have a range between less than or equal to or less than any one of the above upper limits and greater than or equal to or greater than any one of the above lower limits. The AC impedance resistance was measured in the manner described in "7. Interface resistance (AC impedance resistance)" of Examples in this specification.

[0100] Since the copolymer exhibits direct current resistance and / or alternating current impedance resistance, a secondary battery or an electrode assembly to which the copolymer is applied may be stably operated or stored in a normal state.

[0101] The copolymers can exhibit a PTC effect tailored to the target.

[0102] For example, the copolymer may exhibit a property that ΔR1 of the following Equation 1 is within a predetermined range.

[0103] [Equation 1]

[0104] ΔR1=Max{(R n+5 / R n ) / 5}

[0105] In Equation 1, R n is the DC resistance at any temperature n°C in the range of 25°C to 135°C, R n+5 It is the DC resistance at a temperature 5℃ higher than temperature n℃ ((n+5)℃), Max{(R n+5 / R n ) / 5} is confirmed in the temperature range of 25℃ to 135℃ (R n+5 / R n ) / 5 values.

[0106] ΔR1 of equation 1 was measured for the button cell to which the copolymer was applied, and its specific method is described in "8. Measurement of Maximum Resistance Change Rate (DC Resistance)" of the embodiment. In the method for confirming ΔR1, the initial temperature was 25°C and the final temperature was 135°C. n+5 and R n is confirmed by measuring the DC resistance at each temperature while increasing the temperature by 5°C from the initial temperature of 25°C. For example, when n is 90, R 95 / R 90 It is the ratio of the DC resistance at 95° C. to the DC resistance at 90° C. The fact that ΔR1 is 100 Ω·cm / ° C. or more at any temperature in the temperature range of 25° C. to 135° C. means that the resistance increases relatively rapidly at any temperature in the temperature range.

[0107] The lower limit of ΔR1 may be about 100, 150 or 200, and the upper limit thereof may be about 1,000, 950, 900, 850, 800, 750, 700, 650, 600, 550, 500, 450, 400, 350, 300, 250 or 200. The unit of ΔR1 is Ω·cm / ℃. ΔR1 may be within a range greater than or equal to or greater than any one of the above lower limits; or it may have a range between less than or equal to or less than any one of the above upper limits and greater than or equal to or greater than any one of the above lower limits. Through the above characteristics, the electrode to which the copolymer is applied can ensure the stability of the secondary battery, etc. under abnormal conditions.

[0108] Determine the lower limit of the temperature of ΔR1, that is, R nThe temperature at the temperature may be about 81°C, 82°C, 83°C, 84°C, 85°C, 86°C, 87°C, 88°C, 89°C, 90°C, 91°C, 92°C, 93°C, 94°C or 95°C, and the upper limit may be about 200°C, 190°C, 180°C, 170°C, 160°C, 150°C, 140°C, 130°C, 120°C, 110°C, 100°C or 95°C. The temperature may be in a range less than or equal to or less than any one of the above upper limits; or in a range greater than or equal to or greater than any one of the above lower limits; or may have a range between less than or equal to or less than any one of the above upper limits and greater than or equal to or greater than any one of the above lower limits. The temperature is adjusted to a temperature at which an abnormal state occurs or there is a risk of an abnormal state occurring. When a copolymer exhibiting such characteristics is applied, an electrode, an electrode assembly, or a secondary battery can ensure stability under abnormal conditions while maintaining stable performance even in the case of storage in a normal state at a relatively high temperature and in a charge and discharge state at a high temperature.

[0109] The copolymer may exhibit a property that ΔR2 of the following Equation 2 is within a predetermined range.

[0110] [Equation 2]

[0111] ΔR2=Max{(R z+5 / R z ) / 5}

[0112] In Equation 2, R z R is the AC impedance resistance at any temperature n°C in the range of 25°C to 135°C. z+5 is the AC impedance resistance at a temperature 5°C higher than temperature n°C ((n+5)°C), Max{(R z+5 / R z ) / 5} is confirmed in the temperature range of 25℃ to 135℃ (R z+5 / R z ) / 5 values.

[0113] ΔR2 of equation 2 was measured for the button cell to which the copolymer was applied, and its specific method is described in "9. Measurement of Maximum Resistance Change Rate (AC Impedance)" of the embodiment. In the method for confirming ΔR2, the initial temperature was 25°C and the final temperature was 135°C. z+5 and R z It is confirmed by measuring the AC impedance resistance at each temperature while increasing the temperature by 5°C from the initial temperature of 25°C. For example, when n is 90, R 95 / R 90It is the ratio of the AC impedance resistance at 95° C. to the AC impedance resistance at 90° C. The fact that ΔR2 is 10Ω / ° C. or more at any temperature in the temperature range of 25° C. to 135° C. means that the resistance of the copolymer increases relatively rapidly at any temperature in the temperature range.

[0114] The lower limit of ΔR2 can be about 10, 12, 14, 16, 18, 20, 22 or 24, and the upper limit can be about 100, 95, 90, 85, 80, 75, 70, 65, 60, 55, 50, 45, 40, 35, 30, 25 or 24. The unit of ΔR2 is Ω / ℃. ΔR2 can be less than or equal to, or less than any one of the above upper limits, or can be greater than or equal to, or greater than any one of the above lower limits, or can also have a range between less than or equal to, or less than any one of the above upper limits and greater than or equal to, or greater than any one of the above lower limits. Through the above characteristics, the electrode using the copolymer can ensure the stability of the secondary battery, etc. under abnormal conditions.

[0115] Confirm the temperature of ΔR2 in the above range, that is, R z The lower limit of the temperature at may be about 80°C, 81°C, 82°C, 83°C, 84°C, 85°C, 86°C, 87°C, 88°C, 89°C, 90°C, 91°C, 92°C, 93°C, 94°C or 95°C, and the upper limit may be about 200°C, 190°C, 180°C, 170°C, 160°C, 150°C, 140°C, 130°C, 120°C, 110°C, 100°C or 95°C. The temperature may be in a range less than or equal to or less than any one of the above upper limits; or in a range greater than or equal to or greater than any one of the above lower limits; or may also have a range between less than or equal to or less than any one of the above upper limits and greater than or equal to or greater than any one of the above lower limits. The temperature is adjusted to a temperature at which an abnormal state occurs or there is a risk of an abnormal state occurring. When a copolymer exhibiting such characteristics is applied, an electrode, an electrode assembly, or a secondary battery can ensure stability under abnormal conditions while maintaining stable performance even in the case of storage in a normal state at a relatively high temperature and in a charge and discharge state at a high temperature.

[0116] The present specification discloses a current collector for an electrode or an electrode using the copolymer.

[0117] A current collector for an electrode may include a current collector body and a polymer layer formed on the body. The polymer layer may include the above-mentioned copolymer.

[0118] The current collector for an electrode may be used to form an electrode. For example, an electrode formed using the current collector for an electrode may include the current collector for an electrode and an active material layer formed on the polymer layer of the current collector. Figure 1 is a diagram showing an electrode in which an active material layer (300) is formed on a polymer layer (200) of a current collector for an electrode including a current collector body (100) and a polymer layer (200).

[0119] As shown in the accompanying drawings, in the current collector or electrode for the electrode, the current collector body (100) and the polymer layer (200), as well as the polymer layer (200) and the active material layer (300) may also be in contact with each other, and other elements may also be present between them. In addition, although the accompanying drawings show the case where the active material layer (300) is present only on one side of the current collector body (100), the active material layer (300) may also be present on both sides of the current collector body (100). In this case, the polymer layer (200) may also exist in two layers between each of the active material layers (300) present on both sides of the current collector body (100) and the current collector body (100), and may also exist in one layer between any one of the active material layers (300) present on both sides and the current collector body (100).

[0120] The electrode formed with the current collector for the electrode may be a positive electrode (anode) or a negative electrode (cathode) applied to a secondary battery.

[0121] In the current collector for an electrode and the electrode, the polymer layer includes the above copolymer, and thus, stable operation or maintenance in a normal state and stability in an abnormal state can be ensured.

[0122] In the electrode, in order to achieve this purpose more effectively, the oxidation potential relationship between the active material layer formed on the polymer layer or the electrode active material contained therein and the polymer layer or the copolymer contained therein may be adjusted.

[0123] For example, in the electrode, the oxidation potential of the active material layer or the electrode active material may be adjusted to be higher than the oxidation potential of the polymer layer or the copolymer.

[0124] For example, in the electrode, the RV of the following Equation 3 may be within a predetermined range.

[0125] [Equation 3]

[0126] RV=100×Va / Vp

[0127] In Equation 3, Va is the oxidation potential of the electrode active material or active material layer, and Vp is the oxidation potential of the copolymer or polymer layer.

[0128] The oxidation potentials Va and Vp are relative to the oxidation potential of lithium, which are based on the relationship between lithium and lithium ions (Li / Li + The method for measuring the oxidation potential Vp is described in “4. Method for measuring the oxidation potential of copolymer” in the Examples section of this specification, and the method for measuring the oxidation potential Va is described in “5. Method for measuring the oxidation potential of electrode active material” in the Examples section of this specification.

[0129] The lower limit of RV in Equation 3 may be about 100.5, 101, 101.5, 102, 102.5, 103, 103.5, 104, or 104.5, and the upper limit thereof may be about 200, 150, 145, 140, 135, 130, 125, 120, 115, 110, 109, 108, 107, 106, or 105. RV may be in a range greater than or equal to or greater than any one of the above lower limits; or may have a range between less than or equal to or less than any one of the above upper limits and greater than or equal to or greater than any one of the above lower limits.

[0130] If the oxidation potential Va of the active material layer or the electrode active material has the range of RV of the above equation 3, it is not particularly limited. For example, the lower limit of the oxidation potential Va may be about 2.0V, 2.1V, 2.2V, 2.3V, 2.4V, 2.5V, 2.6V, 2.7V, 2.8V, 2.9V, 3V, 3.1V, 3.2V, 3.3V, 3.4V, 3.5V, 3.6V, 3.7V, 3.8V, 3.9V or 4.0V, and the upper limit thereof may be about 5V, 4.9V, 4.8V, 4.7V, 4.6V, 4.5V, 4.4V, 4.3V, 4.2V or 4.1V. The oxidation potential may be in a range of less than or equal to or less than any one of the above upper limits; or in a range of greater than or equal to or greater than any one of the above lower limits; or may have a range between less than or equal to or less than any one of the above upper limits and greater than or equal to or greater than any one of the above lower limits.

[0131] There is no particular limitation on the current collector applied to the electrode or the current collector body of the electrode, and a current collector body generally used as a current collector body for a positive electrode or a negative electrode may be used.

[0132] If the current collector body has conductivity and does not cause chemical changes in the applied device such as a secondary battery, there is no particular limitation on its type, size, shape, etc. Examples of materials that can be used as the current collector body can be illustrated by materials in which the surface of copper, aluminum or stainless steel is surface-treated with carbon, nickel, titanium or silver, etc. The current collector body can be in the form of a film, sheet, foil, net, porous body, foam or non-woven fabric including the above materials. In some cases, known surface treatments can also be performed on the surface of the current collector body to improve adhesion to other layers such as polymer layers or active material layers.

[0133] Such a current collector body may generally have a thickness in the range of 3 μm to 500 μm, but is not limited thereto.

[0134] The layer usually applied can serve as the active material layer.

[0135] Typically, the active material layer includes an electrode active material. There is no particular limitation on the specific type of the electrode active material, and generally, materials that form a positive electrode or a negative electrode can be used.

[0136] For example, when the active material layer is a positive electrode active material layer, the electrode active material may include: a layered compound such as lithium cobalt oxide (LiCoO2) or lithium nickel oxide (LiNiO2), or a compound substituted with one or more transition metals; a lithium iron oxide such as LiFe3O4; a lithium manganese oxide such as Li 1+c1 Mn 2-c1 O4 (0≤c1≤0.33), LiMnO3, LiMn2O3 or LiMnO2; lithium copper oxide (Li2CuO2); vanadium oxide such as LiV3O8, V2O5 or Cu2V2O7; LiNi 1- c2 M c2 Ni-site lithium nickel oxide represented by O2 (wherein M is at least one selected from Co, Mn, Al, Cu, Fe, Mg, B and Ga, and satisfies 0.01≤c2≤0.3); LiMn 2-c3 M c3 Lithium manganese composite oxides represented by Li2Mn3MO8 (wherein M is at least one selected from Co, Ni, Fe, Cr, Zn and Ta, and satisfies 0.01≤c3≤0.1) or Li2Mn3MO8 (wherein M is at least one selected from Fe, Co, Ni, Cu and Zn); lithium nickel cobalt manganese (NCM) composite oxides, lithium nickel cobalt manganese aluminum (NCMA) composite oxides, and LiMn2O4 in which a portion of Li in the formula is substituted by alkaline earth metal ions, etc., but are not limited thereto.

[0137] When the active material layer is a negative electrode active material layer, as the electrode active material, for example, a compound capable of reversibly inserting and deinserting lithium can be used. Specific examples may include carbonaceous materials such as artificial graphite, natural graphite, graphitized carbon fiber, and amorphous carbon; metal compounds capable of alloying with lithium, such as Si, Al, Sn, Pb, Zn, Bi, In, Mg, Ga, Cd, Si alloy, Sn alloy, or Al alloy; metal oxides capable of doping and dedoping lithium, such as SiO a (0<a<2), SnO2, vanadium oxide and lithium vanadium oxide; or a composite containing a metal compound and a carbonaceous material, such as a Si-C composite or a Sn-C composite, etc., and any one of the foregoing or a mixture of two or more thereof can be used.

[0138] Metal lithium thin film can also be used as negative electrode active material, and as carbon material, low crystalline carbon and high crystalline carbon etc. can also be used. As low crystalline carbon, soft carbon and hard carbon are representative, as high crystalline carbon, high temperature roasted carbon such as amorphous, plate-like, scaly, spherical or fibrous natural graphite or artificial graphite, condensed graphite (Kish graphite), pyrolytic carbon, mesophase pitch type carbon fiber, mesophase carbon microbeads, mesophase pitch, and coke derived from petroleum and coal tar pitch are representative.

[0139] The electrode active material may be contained in the active material layer in a range of about 40 wt % to 99.5 wt % relative to the total weight of the active material layer, but the ratio may be changed according to the purpose or design of the electrode.

[0140] The active material layer may further include a binder. The binder is used to improve the adhesion between the active materials and the adhesion between the active material layer and the current collector body. There is no particular limitation on the example of the binder, and it can be selected from and used, for example, PVDF (polyvinylidene fluoride), PVA (polyvinyl alcohol), SBR (styrene butadiene rubber), PEO (polyethylene oxide), CMC (carboxymethyl cellulose), cellulose acetate, cellulose acetate butyrate, cellulose acetate propionate, cyanoethyl pullulan, cyanoethyl polyvinyl alcohol, cyanoethyl cellulose, cyanoethyl sucrose, pullulan, polymethyl methacrylate, polybutyl acrylate, polyacrylonitrile, polyvinyl pyrrolidone, polyvinyl acetate, ethylene-vinyl acetate copolymer (polyethylene-co-vinyl acetate) and one or more of polyarylate.

[0141] In one example, the binder may be included in the active material layer in a range of 0.1 parts by weight to 10 parts by weight relative to 100 parts by weight of the electrode active material, but is not limited thereto.

[0142] As required, the active material layer may further include a conductive material. If the conductive material has conductivity and does not cause chemical changes in the secondary battery, there is no particular limitation, and any known material can be used. For example, graphite such as natural graphite or artificial graphite; carbon black such as carbon black, acetylene black, Ketjen black, channel black, furnace black, lamp black or thermal black; conductive fibers such as carbon fibers or metal fibers; conductive tubes such as carbon nanotubes (CNTs); metal powders such as fluorocarbons, aluminum or nickel powders; conductive whiskers such as zinc oxide or potassium titanate; conductive metal oxides such as titanium oxide; conductive materials such as polyphenylene derivatives, etc.

[0143] In one example, the conductive material may be included in the active material layer in an amount of 0.1 parts by weight to 20 parts by weight relative to 100 parts by weight of the electrode active material, but is not limited thereto.

[0144] The active material layer may optionally further contain any necessary known components in addition to the above-mentioned components.

[0145] The polymer layer present on the current collector body may include a copolymer. The polymer layer may consist of only a copolymer, or may further include any other necessary additives in addition to the copolymer. The desired electrode can be effectively formed by using the copolymer. In one example, based on the total weight of the polymer layer, the lower limit of the content of the copolymer in the polymer layer may be about 30 wt%, 35 wt%, 40 wt%, 45 wt%, 50 wt%, 55 wt%, 60 wt%, 65 wt%, 70 wt%, 75 wt%, 80 wt%, 85 wt%, 90 wt% or 95 wt%, and the upper limit may be about 100 wt%, 95 wt%, 90 wt% or 85 wt%. The ratio is based on the total weight of the polymer layer. The range of the ratio may be less than or equal to or less than any one of the above upper limits; or greater than or equal to or greater than any one of the above lower limits; or it may also have a range between less than or equal to or less than any one of the above upper limits and greater than or equal to or greater than any one of the above lower limits.

[0146] The thickness of the polymer layer can be appropriately controlled according to the purpose. For example, the lower limit of the thickness can be about 10nm, 50nm, 100nm, 150nm or 200nm, and the upper limit can be about 2μm, 1.5μm, 1μm, 950nm, 900nm, 850nm, 800nm, 750nm, 700nm, 650nm, 600nm, 550nm, 500nm, 450nm, 400nm, 350nm or 300nm. The thickness can be less than or equal to or less than any one of the above upper limits; or in a range greater than or equal to or greater than any one of the above lower limits; or it can also have a range between less than or equal to or less than any one of the above upper limits and greater than or equal to or greater than any one of the above lower limits. The thickness can be measured in the manner described in "3. Thickness Measurement" of the Examples section in this specification.

[0147] This specification also discloses a method for manufacturing a current collector for an electrode or an electrode.

[0148] The method of manufacturing the current collector for an electrode of the present application may include the step of forming a polymer layer on the current collector body, and the method of manufacturing the electrode may include the step of forming an active material layer on the polymer layer.

[0149] There is no particular limitation on the method of forming the polymer layer on the current collector body. For example, the polymer layer can be formed by diluting the above conductive polymer and other additives as needed in an appropriate solvent to prepare a coating liquid, coating the liquid on the current collector, and then drying it.

[0150] In another example, the polymer layer may also be formed by directly polymerizing monomers forming a conductive polymer on the current collector body.

[0151] There are no particular restrictions on the method for preparing the coating composition for forming the polymer layer and the coating method thereof, and the method in the known coating method can be applied. In addition, there are no particular restrictions on the method for polymerizing the conductive polymer, and the known method can be applied. For example, as a method for preparing polythiophene, a method using an oxidative polymerization reaction or a method using a free radical reaction is generally known, and such a method can also be applied to the process for forming the conductive polymer in the present application.

[0152] The prepared coating composition can be used to form a polymer layer on the current collector body. This method can generally include the steps of applying the coating composition on the current collector body and heat treating the applied coating composition. In this method, the properties of the polymer layer can also be controlled by the conditions of the heat treatment.

[0153] For example, the temperature T of the heat treatment and / or the time H of the heat treatment may be controlled.

[0154] For example, the lower limit of the temperature T may be about 50°C, 55°C, 60°C, 65°C, 70°C, 75°C, 80°C, 85°C, 90°C, 95°C, 100°C, 105°C, 110°C, 115°C, 120°C, 125°C, 130°C, 135°C or 140°C, and the upper limit thereof may be 300°C, 295°C, 290°C, 285°C, 280°C, 275°C, 270°C, 285°C, 290°C, 29 ... The temperature may be in a range of less than or equal to or less than any one of the above upper limits; or in a range of greater than or equal to or greater than any one of the above lower limits; or may have a range between less than or equal to or less than any one of the above upper limits and greater than or equal to or greater than any one of the above lower limits. Within this range, the alignment state of the hydrocarbon groups in the conductive copolymer can be appropriately adjusted, and thus, the desired performance can be ensured.

[0155] To achieve this purpose, the product (T×H) of the heat treatment temperature T and the time H may be adjusted. For example, the lower limit of the product (T×H) of the heat treatment temperature T and the time H may be 0.01°C·hour, 0.05°C·hour, 0.1°C·hour, 0.2°C·hour, 0.3°C·hour, 0.5°C·hour, 1°C·hour, 5°C·hour, 10°C·hour, 15°C·hour, 20°C·hour, 25°C·hour, 30°C·hour, 35°C·hour, 40°C·hour, 45°C·hour, 50°C·hour, 75°C·hour, 100°C·hour, 110°C·hour, 120°C·hour or 130°C·hour. Hours, and the upper limit can be 100000℃·hour, 95000℃·hour, 90000℃·hour, 85000℃·hour, 80000℃·hour, 75000℃·hour, 70000℃·hour, 65000℃·hour, 60000℃·hour, 55000℃·hour, 50000℃·hour, 45000℃·hour, 40000℃·hour, 35000℃·hour, 30000℃·hour, 25000℃·hour, 20000℃·hour, 15000℃·hour. · hours, 10000℃· hours, 9500℃· hours, 9000℃· hours, 8500℃· hours, 8000℃· hours, 7500℃· hours, 7000℃· hours, 6500℃· hours, 6000℃· hours, 5500℃· hours, 5000℃· hours, 4500℃· hours, 4000℃· hours, 3500℃· hours, 3000℃· hours, 2500℃· hours, 2000℃· hours, 1500℃· hours, 1400℃· hours, 1300℃· hours, 120 0℃·hour, 1100℃·hour, 1000℃·hour, 900℃·hour, 800℃·hour, 700℃·hour, 600℃·hour, 500℃·hour, 400℃·hour, 300℃·hour, 200℃·hour, 100℃·hour, 90℃·hour, 80℃·hour, 70℃·hour, 60℃·hour, 50℃·hour, 45℃·hour, 40℃·hour, 35℃·hour, 30℃·hour, 25℃·hour, 20℃·hour, 15℃·hour or about 10℃·hour. The product (T×H) may be in a range less than or equal to or less than any one of the above upper limits; or in a range greater than or equal to or greater than any one of the above lower limits; or may have a range between less than or equal to or less than any one of the above upper limits and greater than or equal to or greater than any one of the above lower limits. Within this range, the arrangement state of the hydrocarbon groups in the conductive copolymer can be appropriately adjusted, and thus desired properties can be ensured.

[0156] To more effectively ensure the desired properties, heat treatment can be performed in two steps.

[0157] For example, the heat treatment may include a step of primarily heat treating the coating composition at a first temperature T1 for a first time H1, and a step of secondary heat treating the coating composition at a second temperature T2 for a second time H2, wherein the temperatures T1 and T2 are different from each other, and / or the times H1 and H2 are different from each other.

[0158] For example, the lower limit of the temperature T1 may be about 50°C, 55°C, 60°C, 65°C, 70°C, 75°C, 80°C, 85°C, 90°C, 95°C, 100°C, 105°C, 110°C, 115°C, 120°C, 125°C, 130°C, 135°C or 140°C, and the upper limit thereof may be 300°C, 295°C, 290°C, 285°C, 280°C, 275°C, The temperature may be in a range of less than or equal to or less than any one of the above upper limits; or in a range of greater than or equal to or greater than any one of the above lower limits; or may have a range between less than or equal to or less than any one of the above upper limits and greater than or equal to or greater than any one of the above lower limits. Within this range, the arrangement state of the hydrocarbon groups in the conductive copolymer can be appropriately adjusted, and thus, the desired performance can be ensured.

[0159] For example, the lower limit of the product of the temperature T1 and the time H1 of the initial heat treatment (T1×H1) may be about 0.01°C·hour, 0.05°C·hour, 0.1°C·hour, 0.2°C·hour, 0.3°C·hour, 1°C·hour, 2°C·hour, 3°C·hour, 4°C·hour, 5°C·hour, 6°C·hour, 7°C·hour, 8°C·hour or 9°C·hour, and the upper limit may be 1000°C·hour, 900°C·hour, 800℃·hour, 700℃·hour, 600℃·hour, 500℃·hour, 400℃·hour, 300℃·hour, 200℃·hour, 100℃·hour, 90℃·hour, 80℃·hour, 70℃·hour, 60℃·hour, 50℃·hour, 45℃·hour, 40℃·hour, 35℃·hour, 30℃·hour, 25℃·hour, 20℃·hour, 15℃·hour or about 10℃·hour. The product (T1×H1) may be in a range of less than or equal to or less than any one of the above upper limits; or in a range of greater than or equal to or greater than any one of the above lower limits; or may have a range between less than or equal to or less than any one of the above upper limits and greater than or equal to or greater than any one of the above lower limits. Within this range, the arrangement state of the hydrocarbon groups in the conductive copolymer can be appropriately adjusted, and therefore, the desired performance can be ensured.

[0160] For example, the lower limit of the heat treatment temperature T2 of the secondary heat treatment may be about 50°C, 55°C, 60°C, 65°C, 70°C, 75°C, 80°C, 85°C, 90°C, 95°C, 100°C, 105°C, 110°C, 115°C, 120°C, 125°C or 130°C, and the upper limit thereof may be 300°C, 295°C, 290°C, 285°C, 280°C, 275°C, 270°C, 295°C, 290°C, 285°C, 280°C, 295°C, 29 ... The temperature may be in a range of less than or equal to or less than any one of the above upper limits; or in a range of greater than or equal to or greater than any one of the above lower limits; or may have a range between less than or equal to or less than any one of the above upper limits and greater than or equal to or greater than any one of the above lower limits. Within this range, the arrangement state of the hydrocarbon groups in the conductive copolymer can be appropriately adjusted, and thus, the desired performance can be ensured.

[0161] The product of the secondary heat treatment temperature T2 and the time H2 (T2×H2) can be adjusted. For example, the lower limit of the product of the heat treatment temperature T and the time H (T2×H2) can be about 10℃·hour, 15℃·hour, 20℃·hour, 25℃·hour, 30℃·hour, 35℃·hour, 40℃·hour, 45℃·hour, 50℃·hour, 75℃·hour, 100℃·hour, 110℃·hour, 120℃·hour or 130℃·hour, and the upper limit can also be about 1000℃·hour, 900℃·hour, 800℃·hour, 700℃·hour, 600℃·hour, 500℃·hour, 400℃·hour, 300℃·hour, 200℃·hour, 180℃·hour, 160℃·hour, 150℃·hour, 145℃·hour, 140℃·hour, 135℃·hour or 130℃·hour. The product (T2×H2) may be in a range of less than or equal to or less than any one of the above upper limits; or in a range of greater than or equal to or greater than any one of the above lower limits; or may have a range between less than or equal to or less than any one of the above upper limits and greater than or equal to or greater than any one of the above lower limits. Within this range, the arrangement state of the hydrocarbon groups in the conductive copolymer can be appropriately adjusted, and therefore, the desired performance can be ensured.

[0162] In the above case, the lower limit of the ratio T1 / T2 of the temperature T1 of the primary heat treatment to the temperature T2 of the secondary heat treatment may be about 0.1, 0.3, 0.5, 0.7, 0.9, 0.95, 1, 1.01, 1.02, 1.03, 1.04, 1.05, 1.06 or 1.07, and the upper limit thereof may be about 10, 9, 8, 7, 6, 5, 4, 3, 2, 1.9, 1.8, 1.7, 1.6, 1.5, 1.4, 1.3, 1.2 or 1.1. The ratio T1 / T2 may be in a range less than or equal to or less than any one of the above upper limits; or in a range greater than or equal to or greater than any one of the above lower limits; or may have a range between less than or equal to or less than any one of the above upper limits and greater than or equal to or greater than any one of the above lower limits. Within this range, the arrangement state of the hydrocarbon groups in the conductive copolymer can be appropriately adjusted, and thus, the desired properties can be ensured.

[0163] In the above case, the lower limit of the ratio H2 / H1 of the time H1 of the primary heat treatment to the time H2 of the secondary heat treatment may be about 0.5, 1, 3, 5, 7, 9, 10, 11, 12, 13, 14, 14.5 or 15, and the upper limit thereof may be about 100, 95, 90, 85, 80, 75, 70, 65, 60, 55, 50, 45, 40, 35, 30, 25, 20, 19, 18, 17, 16, 15.5 or 15. The ratio H2 / H1 may be in a range less than or equal to or less than any one of the above upper limits; or in a range greater than or equal to or greater than any one of the above lower limits; or may have a range between less than or equal to or less than any one of the above upper limits and greater than or equal to or greater than any one of the above lower limits. Within this range, the arrangement state of the hydrocarbon groups in the conductive copolymer can be appropriately adjusted, and therefore, the desired characteristics can be ensured.

[0164] In the above-mentioned manufacturing method, after the coating and / or polymerization process, post-treatment such as a proper drying process may be additionally performed.

[0165] Moreover, there is no particular restriction on the method for forming the active material layer on the polymer layer. Generally, the active material layer is formed by coating a slurry comprising an electrode active material, a binder and a conductive material on a current collector (on the polymer layer), followed by drying, and then rolling, and this known method can also be applied to the present application.

[0166] The specification also discloses an electrode assembly or an electrochemical element including the electrode, for example, a secondary battery.

[0167] Beneficial Effects

[0168] The present specification discloses a copolymer and its use. The copolymer can exhibit a PTC (positive temperature coefficient) effect and oxidation potential controlled according to the purpose. This conductive copolymer does not affect or can improve the performance and operation of the secondary battery by exhibiting excellent electrical properties such as low resistance under normal conditions, and can form a current collector, electrode and secondary battery for an electrode including it under abnormal conditions, which can ensure stability. The present specification also discloses a use of the copolymer. BRIEF DESCRIPTION OF THE DRAWINGS

[0169] Figure 1 is a cross-sectional view of an exemplary electrode of the present application.

[0170] Figure 2 These are the results of NMR analysis of the monomers prepared in the preparation examples. DETAILED DESCRIPTION

[0171] Hereinafter, the copolymers and the like disclosed in this specification are specifically described by way of examples and comparative examples. However, the scope of the copolymers is not limited to the following examples.

[0172] 1. NMR analysis method

[0173] 1 1H-NMR analysis was carried out at room temperature (about 25 °C) using an NMR spectrometer, which included a Bruker UltraShield spectrometer (300 MHz) with a 5 mm triple resonance probe. The sample was diluted to a concentration of about 10 mg / ml in a solvent (CDCl3) for NMR measurement and used, and the chemical shift was expressed in ppm.

[0174] 2. GPC (Gel Permeation Chromatography)

[0175] The molecular weight characteristics were measured using GPC (Gel Permeation Chromatography). The sample was placed in a 5 mL vial and diluted to a concentration of about 1 mg / mL with chloroform. Thereafter, the standard sample for calibration and the sample to be analyzed were filtered through a syringe filter (pore size: 0.45 μm) and then measured. As the analysis program, Empower 3 from Waters was used, and the weight-average molecular weight (Mw) and number-average molecular weight (Mn) were obtained by comparing the elution time of the sample with the calibration curve, respectively, and the molecular weight distribution (PDI) was calculated by the ratio (Mw / Mn). The measurement conditions of GPC are as follows.

[0176] <GPC measurement conditions>

[0177] Apparatus: Waters’ 2414

[0178] Column: Use 3 Styragels from Waters

[0179] Solvent: THF (tetrahydrofuran)

[0180] Column temperature: 35 °C

[0181] Sample concentration: 1 mg / mL, 1 μL injection

[0182] Standard sample: Polystyrene (Mp: 3900000, 723000, 316500, 52200, 31400, 7200, 3940, 485)

[0183] 3. Thickness measurement

[0184] The thickness of the polymer layer, etc., was measured by cross-sectioning the electrode using an ion milling device (Hitachi, IM5000) and then taking images with a SEM (scanning electron microscope) (JEOL, JSM-7200F). The conditions for forming the slices by ion milling were performed by setting the device to a slice milling mode, a speed of 3 (reciprocating motion / minute), an accelerating voltage of 6.0 kV, a discharge voltage of 15 kV, a current of 150 μA, and a time of 4 hours.

[0185] 4. Measurement method of oxidation potential of copolymers

[0186] The oxidation potential of the copolymer was measured in the following manner. Using the copolymer whose oxidation potential was to be measured, a layer (hereinafter referred to as a polymer layer) having a thickness of about 10 μm was formed on an aluminum foil (Al foil) having a thickness of about 15 μm. The polymer layer was formed by applying a coating solution prepared by dispersing the copolymer in a solvent (chloroform) at a concentration of about 2.0 wt % on the aluminum foil in a rod coating manner, keeping it at 140° C. for about 4 minutes, and then keeping it at 130° C. for about 60 minutes.

[0187] After that, the separator and the lithium film were laminated on the polymer layer to produce a laminate in which aluminum foil / polymer layer / separator / lithium film was laminated, and the laminate was punched into a circle with a diameter of about 1.4 cm. A button cell was made using the circular punched laminate and an electrolyte (using a Welcos CR2032 button cell kit).

[0188] As a separator, the WL20C model from W Scope of South Korea was used; as a lithium membrane, a membrane with a thickness of about 100 μm was used; as an electrolyte, a 1M LiPF6 solution (solvent: EC / DMC / EMC=3 / 4 / 3 (mass ratio), EC: ethylene carbonate, DMC: dimethyl carbonate, EMC: ethyl methyl carbonate) which is a product of Enchem was used.

[0189] The oxidation potential of the button cell was measured using an electrochemical meter (potentiostat) (Princeton Applied Research, PARASTAT-MC) at 25° C. The oxidation potential was measured by CV (cyclic voltammetry) at a scan rate of 0.17 mV / sec to 0.5 mV / sec in the range of 1.5 V to 5.5 V.

[0190] Based on lithium and lithium ion (Li / Li + ) to measure the oxidation potential.

[0191] 5. Oxidation potential measurement method of electrode active materials

[0192] The oxidation potential of the electrode active material was measured in the following manner.

[0193] An electrode active material layer is formed on an aluminum foil (Al foil) having a thickness of about 15 μm. The active material layer is formed using a slurry. The slurry is prepared by preparing an electrode active material, a conductive material (ECP (Ketjen Black) 0.5%, SFG (Trimrex Graphite) 0.4%, DB (superconductive acetylene black (DenkaBlack)) 0.4%), PVDF (polyvinylidene fluoride) and NMP (N-methyl-2-pyrrolidone) in a weight ratio of 100:16:6:100 (electrode active material: conductive material: PVDF: NMP). The slurry is applied to the aluminum foil with a scraper, dried at room temperature (about 25°C), then kept in a drying oven at 130°C for about 30 minutes, and rolled to form an active material layer having a thickness of about 50 μm to 70 μm.

[0194] As the electrode active material, the electrode active material whose oxidation potential is to be measured is used. The separator and the lithium film are laminated on the active material to produce a laminate in which aluminum foil / active material layer / separator / lithium film are laminated, and the laminate is punched into a circle with a diameter of about 1.4 cm. A button cell is manufactured using the circular punched laminate and an electrolyte (using a Welcos CR2032 button cell kit).

[0195] As a separator, the WL20C model from W Scope of South Korea was used; as a lithium membrane, a membrane with a thickness of about 100 μm was used; as an electrolyte, a 1M LiPF6 solution (solvent: EC / DMC / EMC=3 / 4 / 3 (mass ratio), EC: ethylene carbonate, DMC: dimethyl carbonate, EMC: ethyl methyl carbonate) which is a product of Enchem was used.

[0196] The oxidation potential of the button cell was measured using an electrochemical meter (potentiostat) (manufacturer: Princeton Applied Research, product name: PARASTAT-MC) at 25° C. The oxidation potential was measured by CV (cyclic voltammetry) at a scan rate of 0.17 mV / sec to 0.5 mV / sec in the range of 1.5 V to 5.5 V.

[0197] 6. DC resistance measurement method

[0198] The DC resistance was evaluated using the same button cell as used in "4. Copolymer oxidation potential measurement method." A voltage of 4.3 eV was applied to the button cell for 10 minutes at room temperature (25°C), and the DC resistance was measured using a Fluke digital multi-function tester (FLUKE-87-5).

[0199] 7. Interface resistance (AC impedance resistance)

[0200] The interface resistance was evaluated by EIS (electrochemical impedance spectroscopy) using the same button cell as used in "4. Oxidation potential measurement method of copolymer". A voltage of 4.3 V was applied to the button cell for 10 minutes at room temperature (25° C.), and the interface resistance obtained in the high-frequency region was measured by a Nyquist plot obtained by the EIS measurement method at 50,000 Hz to 0.1 Hz. An electrochemical meter (potentiostat) (Princeton Applied Research, PARASTAT-MC) was used as an EIS measurement device.

[0201] 8. Measurement of maximum resistance change rate (DC resistance)

[0202] The maximum resistance change rate ΔR1 is determined according to Equation 1 below.

[0203] [Equation 1]

[0204] ΔR1=Max{(R n+5 / R n ) / 5}

[0205] ΔR1 is measured in the following manner.

[0206] The button cell for DC resistance measurement (the button cell used in "6. DC resistance measurement method") is placed in the center of a convection oven (Jeotech, OF3-05W), and the oven temperature is set to increase by 5°C per minute, from an initial temperature of 25°C to a final temperature of 135°C. The button cell is connected to a resistance measurement multimeter (Fluke's digital multifunction tester (FLUKE-87-5)) outside the oven to achieve resistance measurement. Subsequently, the DC resistance is measured at each temperature while the temperature is set to increase. That is, the DC resistance is measured at 25°C, 30°C, 35°C, 40°C, 45°C, 50°C, 55°C, 60°C, 65°C, 70°C, 75°C, 80°C, 85°C, 90°C, 95°C, 100°C, 105°C, 110°C, 115°C, 120°C, 125°C and 130°C, respectively. Each temperature is maintained for 1 minute according to the setting content, and the DC resistance is measured after 1 minute at the relevant temperature. The DC resistance at each temperature becomes R in the above equation 1 n , the DC resistance at a temperature 5°C higher than the relevant temperature becomes R in the above equation 1 n+5 In the measured DC resistance, the DC resistance at 25°C, 30°C, 35°C, 40°C, 45°C, 50°C, 55°C, 60°C, 65°C, 70°C, 75°C, 80°C, 85°C, 90°C, 95°C, 100°C, 105°C, 110°C, 115°C, 120°C, and 125°C are each designated as R n, and in the temperature range of 25℃ to 130℃ (R n+5 / R n ) / 5, and then designate the maximum value among them as Max{(R n+5 / R n ) / 5}(=ΔR1), and the maximum value (R n+5 / R n ) / 5 is designated as the on-set temperature.

[0207] 9. Measurement of maximum resistance change rate (AC impedance)

[0208] The maximum resistance change rate ΔR2 is determined according to Equation 2 below.

[0209] [Equation 2]

[0210] ΔR2=Max{(R z+5 / R z ) / 5}

[0211] ΔR2 is measured in the following manner.

[0212] The button cell for AC impedance resistance measurement (the button cell used in "7. Interface resistance (AC impedance resistance)") was placed in the center of a convection oven (Jeotech, OF3-05W), and the temperature of the oven was set to increase by 5°C per minute, from an initial temperature of 25°C to a final temperature of 135°C. The button cell was connected to a resistance measuring device (the measuring device used in "6. Interface resistance (AC impedance resistance)") outside the oven to achieve resistance measurement. Subsequently, while the temperature was raised as set, the AC impedance resistance was measured at each temperature. That is, the AC impedance resistance was measured at 25°C, 30°C, 35°C, 40°C, 45°C, 50°C, 55°C, 60°C, 65°C, 70°C, 75°C, 80°C, 85°C, 90°C, 95°C, 100°C, 105°C, 110°C, 115°C, 120°C, 125°C and 130°C, respectively. According to the setting contents, each temperature is maintained for 1 minute, and the AC impedance resistance is measured at the point where 1 minute has passed at the relevant temperature.

[0213] The AC impedance resistance at each temperature becomes R in the above equation 2 z , the AC impedance resistance at a temperature 5°C above the relevant temperature becomes R of the above equation 2 z+5In the measured AC impedance resistance, the AC impedance resistance at 25°C, 30°C, 35°C, 40°C, 45°C, 50°C, 55°C, 60°C, 65°C, 70°C, 75°C, 80°C, 85°C, 90°C, 95°C, 100°C, 105°C, 110°C, 115°C, 120°C, and 125°C are each designated as R z , obtained in the temperature range of 25℃ to 130℃ (R z+5 / R z ) / 5, and the maximum value among them is designated as Max{(R z+5 / R z ) / 5}(=ΔR2), and the maximum value (R z+5 / R z ) / 5 is designated as the starting temperature.

[0214] The AC impedance resistance was determined as resistance obtained from a semicircle of a high frequency region in a Nyquist plot obtained by applying a voltage of 4.3 V for 10 minutes and measuring using EIS at 50,000 Hz to 0.1 Hz.

[0215] Preparation Example 1. Synthesis of Monomer (A)

[0216] The monomer (A) of the following formula A is synthesized in the following manner.

[0217] [Formula A]

[0218]

[0219] In 100 ml of toluene, 1.372 g (12.02 mmol, 1 equivalent) of 3-methoxythiophene and 3 g (16.83 mmol, 1.4 equivalents) of triethylene glycol monomethyl ether were dissolved together with 230 mg of p-toluenesulfonic acid (p-TsOH) and mixed. While the mixture was refluxed at 120° C. to react (ether exchange reaction), the generated methanol was removed by a 4A type molecular sieve filled in an extractor (Soxhlet extractor). The reactants were refluxed for 24 hours, then quenched with water, extracted with ethyl acetate, then washed with brine, and dried over magnesium sulfate (MgSO4). The solvent was removed using a rotary evaporator, and the residue was purified by column chromatography, eluting with dichloromethane / hexane (2:1) to obtain the target compound (monomer (A)). Figure 2 The results of NMR analysis of the monomer are shown.

[0220] Preparation Example 2. Synthesis of Conductive Copolymer (A)

[0221] Into a solution in which 3.20 g (19.71 mmol, 3 equivalents) of iron (III) chloride was dissolved in 150 ml of dichloromethane, 0.7 g (2.96 mmol, 0.6 equivalents) of 3-dodecylthiophene, 0.3 g (1.48 mmol, 0.3 equivalents) of 3-hexylthiophene, 0.12 g (0.49 mmol, 0.1 equivalents) of the monomer (A) of Preparation Example 1 and 0.37 g (1.64 mmol, 0.3 equivalents) of pyrrole were introduced and polymerized at 25° C. for 24 hours to synthesize a conductive copolymer (A). In the conductive copolymer (A), the molar ratio of the 3-dodecylthiophene unit (I), the 3-hexylthiophene unit (II), the monomer (A) unit of Preparation Example 1 (III) and the pyrrole unit (IV) was 2.96:1.48:0.49:1.23 (I:II:III:IV).

[0222] The polymerization solution was placed in a permeable membrane with a MWCO (molecular weight cut-off) of 5000, and then immersed in 200 ml of acetonitrile solvent to remove unreacted ferric chloride and monomers. The residue precipitated in the permeable membrane was washed with methanol and dried at 60° C. for 12 hours to obtain a conductive copolymer (A). The weight average molecular weight (Mw) and number average molecular weight (Mn) of the conductive copolymer (A) were about 99,000 g / mol and 28,000 g / mol, respectively, and the oxidation potential was about 3.95 V.

[0223] Preparation Example 3. Synthesis of Conductive Copolymer (B)

[0224] Into a solution in which 3.20 g (19.71 mmol, 3 equivalents) of iron (III) chloride was dissolved in 150 ml of dichloromethane, 0.41 g (1.97 mmol, 0.6 equivalents) of 3-dodecylthiophene, 0.24 g (0.98 mmol, 0.3 equivalents) of 3-hexylthiophene, 0.1 g (0.33 mmol, 0.1 equivalents) of the monomer (A) of Preparation Example 1 and 0.74 g (3.28 mmol, 0.3 equivalents) of pyrrole were introduced, and polymerized at 25° C. for 24 hours to synthesize a conductive copolymer (B). In the conductive copolymer (B), the molar ratio of the 3-dodecylthiophene unit (I), the 3-hexylthiophene unit (II), the monomer (A) unit of Preparation Example 1 (III) and the pyrrole unit (IV) was 1.97:0.98:0.33:3.28 (I:II:III:IV).

[0225] The polymerization solution was placed in a permeable membrane with a MWCO (molecular weight cut-off) of 5000, and then immersed in 200 ml of acetonitrile solvent to remove unreacted ferric chloride and monomers. The residue precipitated in the permeable membrane was washed with methanol and dried at 60° C. for 12 hours to obtain a conductive copolymer (B). The weight average molecular weight (Mw) and number average molecular weight (Mn) of the conductive copolymer (B) were about 102,000 g / mol and 25,000 g / mol, respectively, and the oxidation potential was about 3.90 V.

[0226] Preparation Example 4. Synthesis of Conductive Copolymer (C)

[0227] Into a solution in which 3.20 g (19.71 mmol, 3 equivalents) of iron (III) chloride was dissolved in 150 ml of dichloromethane, 1 g (3.94 mmol, 0.6 equivalents) of 3-dodecylthiophene, 0.33 g (1.97 mmol, 0.3 equivalents) of 3-hexylthiophene and 0.16 g (0.66 mmol, 0.1 equivalents) of the monomer (A) of Preparation Example 1 were introduced and polymerized at 30° C. for 24 hours to prepare a conductive copolymer (C). In the conductive copolymer (C), the molar ratio of the 3-dodecylthiophene unit (I), the 3-hexylthiophene unit (II) and the monomer (A) unit (III) of Preparation Example 1 was about 3.94:1.97:0.66 (I:II:III).

[0228] The polymerization solution was placed in a permeable membrane with a MWCO (molecular weight cutoff) of 5000, and then immersed in 200 ml of acetonitrile solvent to remove unreacted iron (III) chloride monomer and low molecular weight oligomers. The residue precipitated in the permeable membrane was washed with methanol and dried at 60° C. for 12 hours to obtain a conductive copolymer (C).

[0229] The conductive copolymer (C) had a weight average molecular weight (Mw) and a number average molecular weight (Mn) of 118,000 g / mol and 24,500 g / mol, respectively, and an oxidation potential of about 4.04 V or so.

[0230] Example 1.

[0231] An aluminum foil having a thickness of about 15 μm is used as a current collector layer. The copolymer (A) of Preparation Example 2 is dispersed in a solvent (chloroform) at a concentration of about 2.0 wt % to prepare a coating solution. The coating solution is applied to the current collector layer in a rod coating manner. Subsequently, the current collector layer on which the coating is formed is kept at 140° C. in a drying oven for about 4 minutes, and again kept at about 130° C. for 1 hour to form a layer (polymer layer) having a thickness of about 200 nm.

[0232] Subsequently, an active material layer is formed on the polymer layer. The active material layer is formed using a slurry. The slurry is prepared by preparing an electrode active material, a conductive material (ECP (Ketjen Black) 0.5%, SFG (Trimrex Graphite) 0.4%, DB (Super Conductive Acetylene Black) 0.4%), PVDF (Polyvinylidene Fluoride) and NMP (N-methyl-2-pyrrolidone) at a solid content ratio of 100:16:6:100 (electrode active material: conductive material: PVDF: NMP). The slurry is applied to the polymer layer with a scraper, dried at room temperature, and then kept in a drying oven at 130°C for about 30 minutes, and then rolled to form it into a thickness of about 60μm.

[0233] As the electrode active material, NCM-based positive electrode active materials (Li[Ni 0.8 Co 0.1 Mn 0.1 ]O2), and the oxidation potential of the active material is about 4.08V.

[0234] Example 2.

[0235] An electrode was manufactured in the same manner as in Example 1, except that the copolymer (B) of Preparation Example 3 was used instead of the copolymer (A) of Preparation Example 2.

[0236] Comparative Example 1.

[0237] An electrode was manufactured in the same manner as in Example 1, except that the copolymer (C) of Preparation Example 4 was used instead of the copolymer (A) of Preparation Example 2.

[0238] Test Example 1. Charge and Discharge Test

[0239] The charge and discharge test was carried out by manufacturing button cells. The button cells were manufactured using a CR2032 standard button cell kit (Welcos CR2032 button cell kit). When manufacturing the button cells, the electrode manufactured in the embodiment or the comparative example was used as the positive electrode, and the lithium film (thickness: about 100 μm) was used as the negative electrode. As an electrolyte, Enchem's product 1M LiPF6 solution (solvent: EC / DMC / EMC=3 / 4 / 3 (mass ratio), EC: ethylene carbonate, DMC: dimethyl carbonate, EMC: ethyl methyl carbonate) was used, and as a separator, a PE (poly (ethylene)) separator (Korea W-Scope, WL20C model) was used.

[0240] The charge and discharge test was performed using a button cell, and the charge and discharge test was performed at room temperature (about 25°C). The initial capacity of the button cell was measured by setting a final charge voltage of 4.5V and a final charge current of 1mA, and charging and discharging at a rate of 0.1C using the CC (constant current) / CV (constant voltage) method. The results are summarized in the 0.1C / 0.1C initial capacity section of Table 1 below. In the relevant part, Ch represents charge and Dch represents discharge.

[0241] Subsequently, the capacity change of the button cell was measured by setting a final charging voltage of 4.5 V and a final charging current of 1 mA, charging at a rate of 0.5 C using the CC (constant current) / CV (constant voltage) method, and discharging under conditions of 0.1 C, 0.5 C, 1 C, and 2 C.

[0242] The results are summarized in the 0.5C Ch (0.5C charge) section of Table 1 below. In the section, 0.1C Dch, 0.5C Dch, 1C Dch, and 2C Dch are the capacities measured when a coin cell charged at 0.5C was discharged under conditions of 0.1C, 0.5C, 1C, and 2C.

[0243] [Table 1]

[0244]

[0245] In Table 1, the reference example is an electrode manufactured in the same manner as in Example 1, which is an electrode manufactured by directly forming an active material layer on a current collector without forming a polymer layer in Example 1. Observing the results in Table 1, Examples 1 and 2 and Comparative Example 1 all show initial capacities similar to those of the reference example. However, in the case of Comparative Example 1, it can be known that the faster the discharge rate in the charge and discharge test, the greater the decrease in capacity.

[0246] On the other hand, even when the discharge rate is fast, Examples 1 and 2 do not show a decrease in capacity, but instead, it can be seen that higher capacity is confirmed compared to the reference example.

[0247] Therefore, it can be confirmed that the electrodes of Examples 1 and 2 can be stably operated in a normal state.

[0248] Test Example 2. PTC Effect Test

[0249] The evaluation results of the DC resistance, interface resistance, etc. of Example 1 are shown in Table 2 below.

[0250] [Table 2]

[0251]

[0252]

[0253] It can be confirmed from Table 2 that all embodiments and comparative examples show appropriate PTC effects. However, in the case of comparative example 1, as in the results of the above-mentioned test example 1, it can be known that the resistance of the SFL increases unexpectedly during discharge, making it difficult to stably operate in a normal state.

[0254] [Explanation of Reference Numbers]

[0255] 100: Current collector body

[0256] 200: Polymer layer

[0257] 300: Active material layer

Claims

1. A copolymer comprising a thiophene unit and a unit of the following formula 3: [Formula 3] in, R5, R6 and R7 are each independently hydrogen, a polar functional group or a hydrocarbon functional group.

2. The copolymer according to claim 1, wherein The polar functional group is a carboxyl group, a hydroxyl group, an amino group, a cyano group, a nitro group, an ether group or a functional group of the following formula 4, and the hydrocarbon functional group is an alkyl group, an alkenyl group, an alkynyl group, an alkoxy group, an alkylcarbonyl group or an alkylcarbonyloxy group: [Formula 4] Wherein, L3 is a single bond, an alkylene group or an alkylidene group, L4 is an alkylene group or an alkylidene group, R8 is hydrogen or an alkyl group, and n is a number in the range of 1 to 10. The copolymer according to claim 1 , having an oxidation potential of 4.00 V or less with respect to lithium. The copolymer according to claim 1 , comprising a thiophene unit having a hydrocarbon functional group as the thiophene unit. 5 . The copolymer according to claim 1 , comprising, as the thiophene units, a first thiophene unit having a hydrocarbon functional group having 10 or more carbon atoms and a second thiophene unit having a hydrocarbon functional group having 9 or less carbon atoms.

6. The copolymer according to claim 5, wherein The hydrocarbon functional group of the first thiophene unit or the second thiophene unit is a linear or branched alkyl, alkenyl or alkynyl group.

7. The copolymer according to claim 5, wherein The ratio of the total molar number of the first thiophene unit and the second thiophene unit is 30 mol % or more.

8. The copolymer according to claim 5, wherein A ratio M2 / M1 of the mole number M2 of the second thiophene unit to the mole number M1 of the first thiophene unit is in the range of 0.01 to 100. 9 . The copolymer according to claim 4 , further comprising a thiophene unit having a polar functional group as the thiophene unit. 10 . The copolymer according to claim 9 , comprising the thiophene unit having a hydrocarbon functional group in an amount of 1 mol to 500 mol per mol of the thiophene unit having a polar functional group. The copolymer according to claim 1 , comprising the unit of Formula 3 in a ratio of 1 mol % to 90 mol %. 12 . The copolymer according to claim 1 , having a direct current resistance of 10,000 Ω·cm or less. 13 . The copolymer according to claim 1 , having an AC impedance resistance of 1,000Ω or less.

14. The copolymer according to claim 1, wherein ΔR1 of the following equation 1 is 100 Ω·cm / °C or more, and it is confirmed that the temperature R of ΔR1 of 100 Ω·cm / °C or more n Is above 80℃: [Equation 1] ΔR1=Max{(R n+5 / R n ) / 5} Among them, R n is the DC resistance at any temperature n°C in the range of 25°C to 135°C, R n+5 It is the DC resistance at a temperature 5℃ higher than temperature n℃ ((n+5)℃), Max{(R n+5 / R n ) / 5} is confirmed in the temperature range of 25℃ to 135℃ (R n+5 / R n ) / 5 values.

15. The copolymer according to claim 1, wherein ΔR2 of the following equation 2 is 10Ω / °C or more, and the temperature at which ΔR2 of 10Ω / °C or more is confirmed is 80°C or more: [Equation 2] ΔR2=Max{(Rz +5 / R z ) / 5} Among them, R z R is the AC impedance resistance at any temperature n°C in the range of 25°C to 135°C. z+5 is the AC impedance resistance at a temperature 5°C higher than temperature n°C ((n+5)°C), Max{(R z+5 / R z ) / 5} is confirmed in the temperature range of 25℃ to 135℃ (R z+5 / R z ) / 5 values.

16. A current collector for an electrode, comprising: a current collector body; and A polymer layer is formed on the current collector body and comprises the copolymer according to any one of claims 1 to 15.

17. An electrode having a current collector body; an active material layer formed on the current collector body and containing an electrode active material; and A polymer layer is formed between the current collector body and the active material layer and comprises the copolymer according to any one of claims 1 to 15.

18. The electrode according to claim 17, wherein The RV of equation 3 below is greater than 100: [Equation 3] RV=100×Va / Vp Herein, Va is the oxidation potential of the electrode active material, and Vp is the oxidation potential of the copolymer or the polymer layer.

19. An electrode assembly comprising the electrode according to claim 17.

20. A secondary battery comprising the electrode according to claim 17.

Citation Information

Patent Citations

  • Insect capture device

    KR1020220134842A